Plant‐made E2 glycoprotein single‐dose vaccine protects pigs against classical swine fever. Issue 2 (10th August 2018) - Laughlin, Richard C.; Madera, Rachel; Peres, Yair; Berquist, Brian R.; Wang, Lihua; Buist, Sterling; Burakova, Yulia; Palle, Sreenath; Chung, Chungwon J.; Rasmussen, Max V.; Martel, Erica; Brake, David A.; et al.
Abstract: Classical Swine Fever Virus (CSFV) causes classical swine fever, a highly contagious hemorrhagic fever affecting both feral and domesticated pigs. Outbreaks of CSF in Europe, Asia, Africa and South America had significant adverse impacts on animal health, food security and the pig industry. The disease is generally contained by prevention of exposure through import restrictions ( e.g . banning import of live pigs and pork products), localized vaccination programmes and culling of infected or at‐risk animals, often at very high cost. Current CSFV‐modified live virus vaccines are protective, but do not allow differentiation of infected from vaccinated animals (DIVA), a critical aspect of disease surveillance programmes. Alternatively, first‐generation subunit vaccines using the viral protein E2 allow for use of DIVA diagnostic tests, but are slow to induce a protective response, provide limited prevention of vertical transmission and may fail to block viral shedding. CSFV E2 subunit vaccines from a baculovirus/insect cell system have been developed for several vaccination campaigns in Europe and Asia. However, this expression system is considered expensive for a veterinary vaccine and is not ideal for wide‐spread deployment. To address the issues of scalability, cost of production and immunogenicity, we have employed an Agrobacterium ‐mediated transient expression platform in Nicotiana benthamiana and formulated the purified antigen in novel oil‐in‐water emulsion adjuvants. We report the manufacturing of adjuvanted, plant‐made CSFV E2 subunit vaccine. The vaccine provided complete protection in challenged pigs, even after single‐dose vaccination, which was accompanied by strong virus neutralization antibody responses.